Tongue Abscess: Case Report - de Carvalho, Thiago Bittencourt Ottoni; Fernandes, Atílio Maximino; Sanches, Raphael Angelo (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The tongue abscesses are rare even being frequently in touch with trauma, bites, and foreign bodies. It occurs because of the immunological features of the saliva and some histological and anatomical characteristics of the tongue. This work has as objective report a case of tongue abscess occurred in our job, and do a literature review.Case Report: Patient of 76 years, male, assisted with complaint of pain when swallowing with progressive evolution for a week, with a significant deterioration over three days. Report history of the surgery, for dental implant in the beginning of the period. In the admission during the oral cavity examination was evident bulging of nearly 2 × 2 cm in the middle third posterior of the right tongue, painful to palpation. Was opted the hospitalization of the patient. Was required a MRI that showed suggestive lesions of abscess in the base of the tongue in the right side. Was submitted to a clinical treatment with antibiotic therapy and surgical drainage. The patient recovered uneventfully.Discussion: The clinical manifestation from the tongue abscess can be varied. The diagnosis must be done by clinic history, correlating risk factors associated, physical exam and the confirmatory imaging exams. The etiology and the differential diagnosis must be considered depending of the place of the clinical manifestation. The approach must include the permeability of airway, clinical support, and systemic antibiotic therapy and abscess drainage.Final Considerations: The abscess of the tongue must go in the differential diagnosis of bulging of the tongue being conducted with the antibiotic therapy and surgical drainage in a daily basis.
Keywords: abscess; tongue diseases; tongue; dental implant